Administrative and legal status of state authorities which supervise and monitor the observance of labor legislation - Melnik, Anna (Actual problems of law (Aktual'ni problemi pravoznavstva), 2018)
The article is devoted to the study of the peculiarities of the administrative and legal status of the subjects of supervision and control over observance of labor legislation